Incidence of cancer in the Coquimbo Region, estimated using biopsy results: 2006 to 2015 - Sarria-Cárcamo, Haylyn; Ramírez-Santana, Muriel (Revista Chilena de Salud Pública, 2021)
Introduction: Though cancers produce a high disease burden in Chile, there is no national population-based cancer registry. The present study aimed to estimate the incidence of the twenty main types of cancers in the Coquimbo Region. Material and methods: Data from the registry of the Unit of Pathological Anatomy of Coquimbo Hospital, which processes all biopsies from public facilities in the region, were used; this allowed for the estimation of the incidence of these pathologies. The different types of cancers were characterized according to the sex and age groups of the affected individuals. For the calculation of incidence rates over two five-year periods, 2006-2010 and 2011-2015, the beneficiary population of the national public health insurance system (FONASA) was used as the denominator. Finally, a linear projection of the incidence rate was calculated until 2025. Results: Women had a higher gross incidence rate of cancer than men. The incidence increases, in both sexes, as age increases. The most incident cancers in women were breast cancer, non-melanoma skin cancer, and cervical cancer, and among men, they were non-melanoma skin cancer, prostate cancer, and gastric cancers. Discussion: Given the relative high frequency of certain cancers (thyroid, testicular, cervical, and breast) among younger adults, preventive strategies should be oriented towards these age groups. Likewise, comprehensive programs should be established for the most frequent cancers (non-melanoma skin, prostate, and colon). If no new cancer prevention policies are implemented, a linear growth of the incidence rate of up to 22% is projected for the year 2025.